Relationship between Serving Leadership and Personality towards Intention to Leave through Work Life Quality - Saripudin; Musa Hubeis; Nancy Yusnita (CV. Ridwan Publisher, 2023)
Quality of Work Life (QWL) is an organizational effort to control employee behavior and maintain work performance so that it improves continuously. The purpose of this study is to investigate the impact of organizational culture, servant leadership, and personality on turnover as mediated by work-life quality. This study used a quantitative approach with a sample size of 134 respondents. Employees of PT Nipindo Primatama Group in North Jakarta City completed questionnaires, which provided the research data. The SmartPLS program was used to analyze the research data using the Structural Equation Modeling (SEM PLS) analysis technique. The findings revealed that organizational culture, servant leadership, and personality all had a significant and positive impact on employees' quality of work life, with the better the organizational culture, servant leadership, and employee personality, the higher the employees' quality of work life. The findings revealed that servant leadership, personality, and work-life quality all had a negative impact on turnover, whereas organizational culture had no direct impact on turnover. Employee turnover can be reduced by servant leadership, personality, and a high quality of work life, whereas a good organizational culture cannot always reduce employee turnover.